2021
DOI: 10.7759/cureus.14055
|View full text |Cite
|
Sign up to set email alerts
|

A Model for an Online Learning Management System for Simulation-Based Acquisition of Psychomotor Skills in Health Professions Education

Abstract: The current coronavirus disease (COVID-19) pandemic has shifted traditional educational approaches in health professions education (HPE) from in-person to remote learning. Although pedagogical strategies have been developed and implemented rapidly to support cognitive and affective domains of learning in HPE, less progress has occurred in psychomotor skills acquisition. Psychomotor skills, referred to as technical skills training, are underpinned by educational theories and conceptual frameworks. Considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 4 publications
(3 reference statements)
0
24
0
Order By: Relevance
“…Before March of 2020, when the World Health Organization declared a coronavirus disease (COVID-19) pandemic, these specific regulated clinical skills were taught and practiced in simulation laboratories. However, during the pandemic, access to these simulation laboratories became limited due to physical distancing, and to continue skills development, other options needed to be considered [ 2 ]. This will be referred to as the decentralized model of simulation-based education (De-SBE), where learners can practice clinical, hands-on skills outside of the simulation laboratories from the comfort of their homes or other locations.…”
Section: Introductionmentioning
confidence: 99%
“…Before March of 2020, when the World Health Organization declared a coronavirus disease (COVID-19) pandemic, these specific regulated clinical skills were taught and practiced in simulation laboratories. However, during the pandemic, access to these simulation laboratories became limited due to physical distancing, and to continue skills development, other options needed to be considered [ 2 ]. This will be referred to as the decentralized model of simulation-based education (De-SBE), where learners can practice clinical, hands-on skills outside of the simulation laboratories from the comfort of their homes or other locations.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for developing the virtual simulation module presented in this technical report is to provide an educational tool for the microtomy procedure so that students can learn and practice the procedure remotely. Numerous studies have suggested that an online learning environment may possess the same learning benefits as face-to-face learning with an instructor present [4,6,10]. Having the learners use this module can increase their training opportunities and ultimately improve learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The virtual simulation module is held on a gamified educational network (GEN), an online learning management system that supports and administers training programs and educational courses. The platform provides gamification elements such as a leaderboard system where participants can rate the quality of others' comments and interactions [6]. The leaderboard system shows the ranking in a private version that does not show the rest of the users who are at each position, which avoids comparisons that could be detrimental to motivation.…”
Section: Inputs and Design Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions 10, 12, 13, 16, 20, 23, and 26 were qualitative and gathered participant comments which are summarized in Table 4 . In general, the features of the maxSIMIO were perceived as realistic and the instructional videos hosted on the GEN platform, an online learning management system designed to teach psychomotor skills [ 12 ], were perceived as educationally useful. Comments provided suggestions for improvements, such as ensuring that maxSIMIO does not roll around when landmarking and performing the IO technique on it, making the bone harder to mimic the anatomical feeling of a human bone and reducing the thickness of the skin.…”
Section: Technical Reportmentioning
confidence: 99%